The Acehnese ornament documentation: a study of ornament elements of Rumoh Aceh of Ibrahim Hasan / Mirza Irwansyah ... [et al.] - Irwansyah, Mirza; Sahputraand, Zulhadi; Arie Edytia, Muhammad Heru; Andeska, Niko (Universiti Teknologi MARA, Perak, 2022)
Rumoh Aceh, Acehnese traditional house, has its original ornament to be preserved. Currently, the existence of ornaments in Aceh houses has begun to be threatened since the declining number of Aceh houses. In addition, the replacement of ornaments on the replica of Aceh houses in Taman Ratu Safiatuddin is quite limited. This paper aims to observe the essential or basic forms of ornaments of Rumoh Aceh elements through collecting data by field observation and tracing as one of the attempts in preserving Acehnese ornaments digitally. The data are traced and analyzed using AutoCad 2019 and Google SketchUp Pro 2019. The data reveals four basic forms of wall ornaments of Ibrahim Hasan’s Rumoh Aceh: squares, rectangles, circles, and triangles. These basic forms are rooted in floral and geometry forms and are used in every Rumoh Aceh. This digital documentation model is proposed to increase interest and make it easier for the next generation, both the general public and construction workers, to study, reconstruct, and develop Acehnese ornaments.